2020
DOI: 10.1159/000506991
|View full text |Cite
|
Sign up to set email alerts
|

High EREG Expression Is Predictive of Better Outcomes in Rectal Cancer Patients Receiving Neoadjuvant Concurrent Chemoradiotherapy

Abstract: Background/Aim: A great proportion of patients with rectal cancer initially present with locally advanced disease and can potentially benefit from neoadjuvant concurrent chemoradiotherapy (CCRT) for downstaging before surgery. However, risk and clinical outcome stratification remain a great challenge. We aimed to find the potential biomarker to predict the effect of neoadjuvant CCRT on rectal cancer. Methods: We identified epiregulin (EREG) as the most significant predictive marker for neoadjuvant CCRT respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Table 1 summarizes the potential functions of EREG. EREG is usually overexpressed in various human cancers such as bladder cancer [ 51 , 52 , 53 ], brain cancer [ 54 , 55 , 56 , 57 ], breast cancer [ 38 , 39 , 58 , 59 , 60 , 61 , 62 , 63 ], ovarian and cervical cancer [ 36 , 64 ], colorectal cancer [ 47 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], head and neck cancer [ 11 , 37 , 73 , 74 , 75 , 76 ], liver cancer [ 77 , 78 ], lung cancer [ 31 , 79 , 80 , 81 , 82 ], pancreatic cancer [ 83 ], prostate cancer [ 84 ], gastric cancer (GC) [ 85 , 86 ], and thymic cancer [ 35 ].…”
Section: The Expression Levels Of Ereg During Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the potential functions of EREG. EREG is usually overexpressed in various human cancers such as bladder cancer [ 51 , 52 , 53 ], brain cancer [ 54 , 55 , 56 , 57 ], breast cancer [ 38 , 39 , 58 , 59 , 60 , 61 , 62 , 63 ], ovarian and cervical cancer [ 36 , 64 ], colorectal cancer [ 47 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], head and neck cancer [ 11 , 37 , 73 , 74 , 75 , 76 ], liver cancer [ 77 , 78 ], lung cancer [ 31 , 79 , 80 , 81 , 82 ], pancreatic cancer [ 83 ], prostate cancer [ 84 ], gastric cancer (GC) [ 85 , 86 ], and thymic cancer [ 35 ].…”
Section: The Expression Levels Of Ereg During Cancer Progressionmentioning
confidence: 99%
“…In addition, high expression of EREG mRNA, but not AREG, was correlated with longer OS and progression-free survival (PFS) in patients with mCRC receiving first-line irinotecan-based chemotherapy [ 68 ]. Moreover, EREG can serve as a potential predictive marker, and high EREG protein levels were associated with better survival outcomes in patients with CRC receiving neoadjuvant concurrent chemoradiotherapy [ 71 ]. Moreover, increased EREG protein expression in patients with glioblastoma was highly correlated with a higher tumor grade and poor OS [ 55 ].…”
Section: The Expression Levels Of Ereg During Cancer Progressionmentioning
confidence: 99%
“…However, whether heavily glycosylated MUC2 can orchestrate REG4 to evade immune elimination needs further validation. In contrast, the epiregulin ( EREG ) gene was one of the top 200 genes that were co-downregulated with MUC2 (Spearman’s correlation: −0.379) ( Supplementary Figure S1B ) and one of the favorable factors among rectal cancer patients receiving CCRT in our previous research [ 27 ]. Collectively, these results indicate that the molecular characterization of rectal cancer is complicated and interactive, and integration of these favorable and unfavorable biomarkers can more precisely guide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Epiregulin is in the EGF family of proteins and is an EGFR agonist. In one study, epiregulin was examined with immunohistochemistry in 172 rectal cancer biopsies collected before neoadjuvant chemoradiotherapy [37]. The study showed that higher epiregulin expression prior to treatment was significantly associated with better disease-specific survival, locoregional recurrence-free survival, and metastasis-free outcome, thus suggesting that epiregulin could be a potential therapeutic target and predictive marker.…”
Section: Dna Mismatch Repairmentioning
confidence: 99%